A global atlas of potential thermal refugia for coral reefs generated by internal gravity waves - Bachman, Scott D.; Kleypas, Joan A.; Erdmann, Mark; Setyawan, Edy (Frontiers in Marine Science, 2022)
Coral reefs are highly threatened by ocean warming and the majority are likely to be lost in less than three decades. A first step in maximizing reef conservation through this period is to identify where coral reefs are more likely to survive rising ocean temperatures, such as locations that experience lower temperatures than surrounding regions, high temperature variability, and high food supply. Such conditions are often the result of naturally occurring internal gravity waves (IGWs), oscillatory subsurface disturbances that can entrain cooler and/or nutrient-rich subsurface waters and cause high frequency temperature fluctuations. These features usually remain undetected because they occur subsurface and at spatial scales of O(1 km) and smaller. To shed light on where IGWs are likely to impact temperature conditions within coral reef regions, we present an analysis of data from the LLC4320, a massive high resolution (1/48˚; < 2.5 km) numerical global ocean simulation. The results highlight strong regional differences in the incidence of IGW-induced temperature variability. The analysis also reveals that thermal refugia are limited to depths where high temperature variability coincides with the actual reef depth and may not persist year-round. Assuming 10-m depth as the nominal reef depth, reef regions likely to benefit from IGW-induced cooling occur in SE Asia and the Coral Triangle, the Galápagos, along the Pacific shelf of Central America, and isolated locations worldwide. Such refugia are rare within the Atlantic reef sector. An interactive global atlas showing the results of this study has been made freely available online at https://ncar.github.io/coral-viz/.